Imaging of glutamate in acute carbon monoxide poisoning using chemical exchange saturation transfer - Zheng, Hongyi; Zheng, Wenbin; Liu, Hongkun; Zhang, Gengbiao; Li, Weijia; Zhuang, Jiayan; Guo, Yuelin (Frontiers in Neurology, 2023)
Aims. This study adopted the Glutamate Chemical Exchange Saturation Transfer (GluCEST) imaging technique to quantitatively analyze the cranial glutamate, and discussed the value of the GluCEST in identifying the pathogenesis of encephalopathy after CO poisoning. Methods. The routine MRI and functional MRI scans of two cohorts of subjects (CO group, n=29; Control group, n=21) were performed. Between-group comparisons were conducted for GluCEST% in regions of interest (ROI), including the basal ganglia, thalamus, frontal lobe, occipital lobe, genu of the corpus callosum, cingulate gyrus and cuneus. Moreover, age-stratified subgroup analysis was devised, and correlational analysis was performed for the GluCEST% with coma days, Simple Mental State Examination Scale (MMSE) score, Hamilton Anxiety Scale score, and blood COHb% in each ROI. Results. As compared to the healthy control, CO group led to significantly increasing GluCEST% in the basal ganglia, occipital lobe, genu of the corpus callosum, cingulate gyrus and cuneus (p<0.05). In subgroup analysis for age, adult patients had higher GluCEST% in the basal ganglia, thalamus, occipital lobe, cingulate gyrus and cuneus, compared with healthy adults (p<0.05). Additionally, the correlational analysis in CO-poisoned patients revealed statistical association between the GluCEST% and MMSE in the thalamus and genu of the corpus callosum. Conclusion. The GluCEST technique is superior to routine MRI that can identify cerebral biochemical changes earlier after acute CO poisoning, which is significant for our understanding on the role of neurotransmitters in the pathological basis of this disease. Brain injury caused by CO poisoning may be different in adults and children.